2023
DOI: 10.3390/ma16072743
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Mixed Minerals with Finite Phase Using Thermal Infrared Hyperspectral Technology

Abstract: It is crucial but challenging to detect intermediate or end products promptly. Traditional chemical detection methods are time-consuming and cannot detect mineral phase content. Thermal infrared hyperspectral (TIH) technology is an effective means of real-time imaging and can precisely capture the emissivity characteristics of objects. This study introduces TIH to estimate the content of potassium salts, with a model based on Competitive Adaptive Reweighted Sampling (CARS) and Partial Least Squares Regression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Figure 12 shows the bending strength as a function of peak welding temperature. It was found that the equation of y = −0.019 x 2 + 5.081x − 200.75 with the correlation coefficient [41] of 0.8857 seems to be an optimum trend equation for predicting the bending strength of the welded part (y) using peak welding temperature (x). Figure 13 shows the comparison of the numerical simulation and experimental results of the peak temperature for RFW of PC and ABS rods at five different rotational speeds.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 12 shows the bending strength as a function of peak welding temperature. It was found that the equation of y = −0.019 x 2 + 5.081x − 200.75 with the correlation coefficient [41] of 0.8857 seems to be an optimum trend equation for predicting the bending strength of the welded part (y) using peak welding temperature (x). Figure 13 shows the comparison of the numerical simulation and experimental results of the peak temperature for RFW of PC and ABS rods at five different rotational speeds.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the effects of the rotational speed of RFW on the fatigue life of welded parts, five different rotational speeds were assessed in this study, i.e., 330, 490, 650, 950, and 1350 rpm. During RFW, the temperature history in the weld joint was recorded using an infrared thermal imager [ 30 ] (BI-TM-F01P, Panrico trading Inc., New Taipei City, Taiwan). Significantly, the temperature history in the weld joint was also predicted using COMSOL Multiphysics software.…”
Section: Methodsmentioning
confidence: 99%
“…The cycle time of RFW was set to 60 s, which includes a frictional time of 30 s, a welding time of 20 s, and a cooling time of 10 s. The welding parameters include axial load of 17 N, feed rate of 0.1 mm/min, and burn-off length of 2 mm. During RFW, the temperature history in the weld joint was recorded using an infrared thermal imager [29] (BI-TM-F01P, Panrico trading Inc., New Taipei City, Taiwan). After RFW, shore A surface hardness tests (MET-HG-A, SEAT Inc., New Taipei City, Taiwan), impact tests (780, Instron Inc., MA, USA), and three-point bending tests (RH-30, Shimadzu Inc., Kyoto, Japan) were carried out to evaluate the mechanical properties of the welded parts.…”
Section: Methodsmentioning
confidence: 99%